2015
DOI: 10.1016/j.bbamem.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane calcium channels in cancer: Alterations and consequences for cell proliferation and migration

Abstract: The study of calcium channels in molecular mechanisms of cancer transformation is still a novel area of research. Several studies, mostly conducted on cancer cell lines, however support the idea that a diversity of plasma membrane channels participates in the remodeling of Ca2+ homeostasis, which regulates various cancer hallmarks such as uncontrolled multiplication and increase in migration and invasion abilities. However few is still understood concerning the intracellular signaling cascades mobilized by cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 88 publications
2
140
0
1
Order By: Relevance
“…In a study concerning prostate cancer, data revealed that transient receptor potential cation channel subfamily V member 6-dependent Ca 2+ influx contributed to prostate cancer development by enhancing proliferation of tumor cells and protecting them from apoptosis (26). Other studies demonstrated that higher plasma membrane channel expression and Ca 2+ influx were associated with increased proliferation and tumor cell migration (27,28). Therefore, we hypothesized that CAPS may promote tumorigenesis and tumor progression by disturbing intracellular Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study concerning prostate cancer, data revealed that transient receptor potential cation channel subfamily V member 6-dependent Ca 2+ influx contributed to prostate cancer development by enhancing proliferation of tumor cells and protecting them from apoptosis (26). Other studies demonstrated that higher plasma membrane channel expression and Ca 2+ influx were associated with increased proliferation and tumor cell migration (27,28). Therefore, we hypothesized that CAPS may promote tumorigenesis and tumor progression by disturbing intracellular Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of intracellular Ca 2þ effectors in turn regulates cellular activities necessary for cell-cycle progression and cell proliferation (5,9). Abnormal expression and activity of Ca 2þ signaling proteins have been suggested to contribute to the highly proliferative capacity of several human cancers (7,9). These include members of the transient receptor potential (TRP) superfamily, which form Ca 2þ entry channels.…”
Section: Introductionmentioning
confidence: 99%
“…When stimulated by extracellular calcium ([Ca 2þ ] o ), CaSR acts through at least two G protein pathways (Gq/ 11 and Gi/o) to regulate cell signaling, including increases in cytosolic Ca 2þ concentration ([Ca 2þ ] cyt ), which can result from Ca 2þ release from internal stores or Ca 2þ entry from extracellular space through Ca 2þ -permeable cation channels. The activation of intracellular Ca 2þ effectors in turn regulates cellular activities necessary for cell-cycle progression and cell proliferation (5,9). Abnormal expression and activity of Ca 2þ signaling proteins have been suggested to contribute to the highly proliferative capacity of several human cancers (7,9).…”
Section: Introductionmentioning
confidence: 99%
“…Channelopathies are involved in a wide range of diseases including epilepsy, migraine, blindness, hypertension, and cardiac arrhythmia [4] . Likewise, ion channel malfunction has been suggested to be involved in altered cell proliferation, migration, apoptosis, and differentiation [1,2,[5][6][7] .…”
Section: Introductionmentioning
confidence: 99%